The Use of Socio-Affective Strategies in Learning Speaking Skills - Sukimin, Anggun Putri Maharani; Sunra, La; Talib, Ahmad (State University of Makassar, 2025)
The study aimed to discover (1) The socio-afffective strategies students use in learning speaking skills. (2) How students applied the socio-affective strategies in learning speaking skills. This study is a type of qualitative research that uses qualitative descriptive methods to collect the data. Interviews and documentation were used as the instruments to collect the data. Five students were selected as participants by using a purposive random sampling technique. This study showed that the students used all types of socio-affective strategies: asking questions, cooperating with others, lowering anxiety, self-reinforcement, self-talk, taking someone’ temperature, empathizing with others, and social-mediating. Eventually, among those socio-affective strategies, the students frequently ask questions, cooperate with others, and engage in self-talk. The researcher concluded that the socio-affective strategies are helpful for them to interact with teachers and friends, build self-confidence, and enhance their knowledge of English, especially in speaking skills.Keywords: Socio-Affective Strategies and Speaking Skills.